(untitled) (Journal of Orofacial Research, 2011)
This study was conducted to asses the relationship between the body mass index and periodontal disease status in vegetarian and mixed diet subjects of Udaipur, Rajasthan, India. This study was conducted to know the periodontal disease status in the vegetarian and mixed diet subjects of Udaipur. Age group of the study population was 35 to 44 years. Two hundred subjects were assessed to know the periodontal disease status by trained and calibrated examiners. Obesity related to visceral fat accumulation, is known to increase the risk of various adult diseases, especially type II diabetes and cardiovascular disease. This study was conducted to clarify the relationship between obesity and periodontitis. Body-mass index (BMI) was significant risk indicator for periodontitis after adjustment for known risk factors (p < 0.002). Higher categories of Body Mass Index significantly increased the adjusted risk of periodontitis compared withsubjects with the lower categories of Body Mass Index. Body mass index has a direct co-relation with periodontal status of the population. Periodontal disease status highly depends on the dietary habits of the population.